2008
DOI: 10.1590/s1516-18462008000300011
|View full text |Cite
|
Sign up to set email alerts
|

Aspectos de religiosidade na saúde vocal de cantores de grupos de louvor

Abstract: REsuMOObjetivo: identificar, em participantes de Grupo de Louvor, aspectos de religiosidade presentes no saber e nas práticas relacionadas ao uso da voz e aos cuidados de saúde vocal. Métodos: pesquisa qualitativa, que envolve dados de desenho e depoimento escrito sobre a voz, questionário aberto e grupo focal, categorizados a partir da análise de conteúdo/análise temática. Resultados: são apresentados a partir das categorias e atributos: sócio-cultural (relação com as pessoas e com Deus), componente essencial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1
14

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 17 publications
0
8
1
14
Order By: Relevance
“…Ana Paula Dassie-Leite (1) , André de Campos Duprat (2) , Roberta Busch (3) RESUMO Objetivo: comparar hábitos de bem estar vocal entre cantores líricos e populares. Métodos: foi realizado um trabalho exploratório descritivo, com a participação de 30 cantores líricos e 30 populares, estudantes da Universidade Livre de Música.…”
Section: A Comparison Between Vocal Habits Of Lyric and Popular Singersunclassified
“…Ana Paula Dassie-Leite (1) , André de Campos Duprat (2) , Roberta Busch (3) RESUMO Objetivo: comparar hábitos de bem estar vocal entre cantores líricos e populares. Métodos: foi realizado um trabalho exploratório descritivo, com a participação de 30 cantores líricos e 30 populares, estudantes da Universidade Livre de Música.…”
Section: A Comparison Between Vocal Habits Of Lyric and Popular Singersunclassified
“…The present study allows to observe that the gospel singers reported complaints are common in this population 10,11 . These data reinforce the importance of proper voice prepare and speech-language following regarding voice care guidance, hydration, and voice exercises practice that may be used before and after singing as warm up and cooling down in order to ease these complaints 9,10,17,27 . Besides, the lack of information about vocal health may contribute to developing laryngeal disturbances and dysphonia through time 11 .…”
Section: Resultsmentioning
confidence: 59%
“…This leads to the observation that all the found data related to vocal complaints and symptoms, as well as the MSHI values, are related to the voice use during gospel singers. According to literature, there is a high index of gospel singers that do not have prepare or proper training 9,17 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One article was excluded as it deals with a case study with the purpose of reflecting on the mother-baby relationship, by means of body therapy associated to the singing voice production, whose participant had experience with classical music (17) . Three articles and one dissertation were located and excluded because they were conducted with singers of gospel music (18)(19)(20)(21) . Thus, there were 20 publications on popular singing (Chart 1).…”
Section: Resultsmentioning
confidence: 99%